Pentingnya Pengesahan Rancangan Undang-Undang Perampasan Aset oleh Dewan Perwakilan Rakyat Republik Indonesia - Adam, Widyarti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
TThis study aims to examine the urgency of enacting the Draft Law on Asset Forfeiture by the People's Representative Council of the Republic of Indonesia and its potential impact upon implementation. The Asset Forfeiture Bill serves as a vital instrument in the ongoing effort to protect the Indonesian people from networks of corrupt actors. It also provides a regulatory framework to streamline the confiscation of assets derived from acts of corruption. The researcher aspires for this study to contribute to strengthening measures for preventing and combating corruption in Indonesia. This research adopts a normative method, drawing extensively on statutory regulations and comprehensive literature analysis.